CD4+ T Cells Mediate Dendritic Cell Licensing to Promote Multi‐Antigen Anti‐Leukemic Immune Response - Luis Gil‐de‐Gómez; Joseph J. Mattei; Jessica H. Lee; Stephan A. Grupp; Gregor S. D. Reid; Alix E. Seif (Cancer Medicine)
ABSTRACT Background Single antigen (Ag)‐targeted immunotherapies for acute lymphoblastic leukemia (ALL) are highly effective; however, up to 50% of patients relapse after these treatments. Most of these relapses lack target Ag expression, suggesting targeting multiple Ags would be advantageous. Materials & Methods The multi‐Ag immune responses to ALL induced by transducing cell lines with xenoAgs green fluorescent protein and firefly luciferase was elucidated using flow cytometry, ELISA, and ELISpot assays. Results In our model, leukemia responsiveness correlates with in vivo CD4+ T cell activation and DC maturation, supporting a role for DC licensing. In contrast, tolerance is characterized by in vivo increased expression of negative immune checkpoints (IC) which may suppress rather than license DC. In vitro assays confirm the ability of CD4+ T cells from leukemia‐responsive mice to promote robust maturation of naïve bone marrow DC in the presence of non‐immunogenic leukemia antigens. Conclusion Together these findings support a CD4+ T cell‐mediated mechanism of DC licensing to promote multi‐Ag immune responses that may augment current targeted immunotherapies and avoid relapses in treated children with ALL.